Peri-Neural Invasion Is an Important Prognostic Factor of T2N0 Oral Cancer - Chi-Sheng Cheng; Chien-Chih Chen; Yi-Chun Liu; Chen-Chi Wang; Yu-Shu Chou (Medicina, 2022)
Background and objectives: Among patients with pathologically proven T2N0 oral squamous cell carcinoma (OSCC), a notable amount of patients still die from tumor recurrence although they have radical surgery for early stage cancers. In literature, the prognostic indicators of this specific disease entity were rarely reported. This study aims at analyzing the prognostic factors of T2N0 OSCC patients and discussing possible managements to improve the survival. Materials and Methods: From January 2012 to December 2017, the data of 166 pathologically proven T2N0 oral cancer patients proved by radical surgery were retrospectively collected. The clinical and pathologic factors including age, gender, tumor differentiation grade, perineural invasion (PNI), angiolymphatic invasion (ALI), margin status, and adjuvant therapy were analyzed by univariate and multivariate analysis to determine their association with disease-specific survival (DSS), and disease-free survival (DFS), which were calculated by Kaplan–Meier method. Results: After median follow up time of 43.5 months, overall 3-year rates of DSS and DFS were 86.1% and 80.1% respectively for our 166 patients. Univariate analysis showed that the 3-year DSS of 90.8% for PNI negative patients was significantly better than DSS of 57.0% for PNI positive patients (p = 0.0006). The 3-year DFS of 84.2% for PNI negative patients was also significantly better than DFS of 54.6% for PNI positive patients (p = 0.001). Further multivariate analysis revealed PNI was the only independent prognostic factor associated with both DSS (Hazard Ratio (HR) = 5.02; 95% Confidence Interval (CI) = 1.99–12.6; p = 0.001), and DFS (HR = 3.92; 95% CI = 1.65–9.32; p = 0.002). Nearly 10% (16) of the 166 patients had adverse pathologic feature of PNI only. In the 11 patients without adjuvant therapy, 5 patients died from OSCC. No patients had recurrence or mortality after they received adjuvant therapy with chemotherapy ± radiotherapy. Conclusion: PNI was an independent prognostic factor for T2N0 oral cancer patients. Adjuvant chemotherapy and radiotherapy may benefit the survival of this specific disease entity, but further investigations are needed to elucidate the optimal regimen.